Documentary control of marine biodiversity in the Gulf of Nicoya, Costa Rica - Largaespada Baltodano, Hilda (2008)
This document summarizes the final work of graduation of the documentary control realized in the topic of marine biodiversity, contemplates a brief contextualization of the situation that presents the control of the bibliographic production on this topic. Subsequently, it refers to the objectives set to carry out the directed practice; it also highlights the literary review process carried out. Finally, it mentions the methodology implemented and the bibliometric analysis of the documentation contained in the Biomarina database.